Single-inhaler triple therapy in symptomatic COPD patients: FULFIL subgroup analyses. Issue 2 (4th May 2018) - Halpin, David M.G.; Birk, Ruby; Brealey, Noushin; Criner, Gerard J.; Dransfield, Mark T.; Hilton, Emma; Lomas, David A.; Zhu, Chang-Qing; Lipson, David A.
Triple inhaled corticosteroid (ICS)/long-acting muscarinic antagonist (LAMA)/long-acting β2 -agonist (LABA) therapy is recommended for symptomatic patients with chronic obstructive pulmonary disease (COPD) and at risk of exacerbations. However, the benefits versus side-effects of triple inhaled therapy for COPD, based on distinct patient clinical profiles, are unclear. FULFIL, a phase III, randomised, double-blind study, compared 24 weeks of once-daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100/62.5/25 µg using the Ellipta inhaler with twice-daily budesonide/formoterol (BUD/FOR) 400/12 µg using the Turbuhaler. Subgroup analyses of forced expiratory volume in 1 s (FEV1 ), St George's Respiratory Questionnaire (SGRQ) Total score and exacerbation rates were carried out. Subgroups were defined by COPD medication at screening (ICS+LABA, BUD+FOR, ICS+LABA+LAMA, LAMA alone, tiotropium alone and LAMA+LABA), by disease severity (lung function and exacerbations) and by exacerbation history (exacerbation severity and frequency). In the intent-to-treat population (n=1810) at week 24, FF/UMEC/VI (n=911) versus BUD/FOR (n=899) improved FEV1 and SGRQ Total score and reduced mean annual exacerbation rates in all disease severity and exacerbation history subgroups. FF/UMEC/VI versus BUD/FOR improved FEV1 and SGRQ Total score in all medication subgroups and reduced mean annual exacerbation rates in all medication subgroups, except LAMA+LABA. Adverse events were similar across subgroups. These findings support the benefit of FF/UMEC/VI compared with dual ICS/LABA therapy in patients with symptomatic COPD regardless of disease severity or prior treatment and may help to inform clinical decision making. Single-inhaler triple therapy for COPD provides clinical benefit across a wide spectrum of disease characteristics http://ow.ly/ETBv30iXQ97